Silica-coated Fe3O4 magnetic nanoparticles-supported sulfonic acid as a highly active and reusable catalyst in chemoselective deprotection of tert-butyldimethylsilyl (TBDMS) ethers. (2nd January 2020) - Hossein Javadi, Sayed; Zareyee, Daryoush; Monfared, Azam; Didehban, Khadijeh; Mirshokraee, Sayed Ahmmad
Abstract: Anchored propyl sulfonic acid on the surface of silica-coated magnetic nanoparticles (Fe3 O4 @SiO2 @PrSO3 H) was successfully employed in the deprotection of TBDMS ethers. The prepared magnetically separable nanocatalyst exhibited efficient catalytic activity with high conversion and selectivity in cleavage of TBDMS ethers. TBDMS ethers are efficiently cleaved to the corresponding hydroxyl compounds in methanol solution containing 2 mol% magnetic nano-catalysts. Good to excellent yields of products, simple work-up and product separation, selective cleavage of TBDMS ethers in the presence of TBDPS ethers, easy recycling of the catalyst with external magnet with no loss in its activity (7 reaction cycles) are important features of this new protocol. Graphical Abstract: